Islamic-based counseling services in developing self-concept of street children in rejang lebong regency - Hartini, Hartini; Fadila, Fadila (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2017)
This study aimed to comprehend and explain the condition of street children's self-concept in Rejang Lebong regency by focusing on Islamic-based counseling services. According to Baldwin and Holmes (in Calhoun and Acocella 1995), the determining factors of self-concept are parents, peers, communities, and learning process. This theory becomes the choice towards the question and purpose of this research. The other background is a factual matter, that in Rejang Lebong regency which has the areas of 1.515.76 Km2, there are massive populations of Moslem, 254 583 people. And has a fairly good kinship culturally. So that the street children should not exist in this country, but in fact, there are 617 children abandoned in this region.This research is mixed. Combining the methods of qualitative and quantitative approach by using experimental methods, and providing various counseling services through Islamic perspective required by street children and in accordance with their problems known by interviews and observations done by the researcher. To notice the effectiveness of counseling services by Islamic perspective in improving street children's self-concept, the researcher gave some questionnaires as the pre-test in advance and ended by giving post-test questionnaires. The number of samples were 36 street children in Rejang Lebong regency. For sampling techniques, the researcher chose purposive sampling method based on predefined criterias, that the sample were street children wanted to follow the interview (indepth-interview) and fill up the questionnaires.Based on the data obtained in the form of street children's self-concept overview, then the Islamic-based counseling services were given. The results of pre-test indicated that the average value of street children's self-concept before being given treatment equal to 84.04, while after being given guidance and counseling services through an Islamic perspective, it was increased to 90.56, while the results of t value are at -11 791 by 0000 sig, Because sig were at <0.05, then we can conclude that Ha was acceptable and it means the street children's self-concept before and after given guidance and counseling services by Islamic perspective were different, thus it can be concluded that the concept of guidance and counseling services through Islamic perspective influenced/enhanced the street children's self-concept .